Diurnal Variations of Below‐Canopy CO2 Concentration in a Subtropical Forested Valley - Shizuo Fu; Yang Wang; Guofang Miao; Rong Wang; Hongda Zeng; Bai Yang; Jing M. Chen (Earth and Space Science)
Abstract CO2 concentration was continuously measured at four levels in the below‐canopy layer of a subtropical evergreen broadleaf forest in Southeast China. The below‐canopy CO2 concentration was higher during the day than at night at all levels, in contrast to many previous studies. The amplitude of the diurnal variation of the below‐canopy CO2 concentration was controlled by the daily‐mean air or soil temperature. In the daytime, solar radiation heated the canopy layer more than the below‐canopy layer, so the below‐canopy layer became stable. Large vertical gradients of CO2 concentration therefore developed near the ground surface. CO2 concentration increased with stability when the stability was weak, because the increased stability suppressed the vertical turbulent mixing. On the contrary, CO2 concentration decreased with stability when the stability was strong, because the strong stability was maintained by intense solar radiation, which enhanced photosynthesis. In the nighttime, radiative cooling of the canopy layer caused the below‐canopy layer to be near‐neutral or unstable. CO2 concentration was therefore generally low and exhibited rather small vertical gradients. Nighttime CO2 concentration slightly increased when the stability became stronger. It was frequently observed that CO2 concentration rapidly decreased around the sunset from the peak value to a low value. Our results suggest that the storage term is important in the daytime eddy‐covariance measurements, and the CO2 concentration above the canopy should be corrected in order to represent the CO2 concentration below the canopy.